MRI evaluation of articular cartilage in patients with juvenile osteochondritis dissecans (JOCD) using T2∗ mapping at 3T. Issue 9 (September 2020) - Ludwig, K.D.; Johnson, C.P.; Zbýň, Š.; Nowacki, A.; Marette, S.; Takahashi, T.; Macalena, J.A.; Nelson, B.J.; Tompkins, M.A.; Carlson, C.S.; Ellermann, J.M.
Summary: Objective: Evaluate articular cartilage by magnetic resonance imaging (MRI) T2∗ mapping within the distal femur and proximal tibia in adolescents with juvenile osteochondritis dissecans (JOCD). Design: JOCD imaging studies acquired between August 2011 and February 2019 with clinical and T2∗ mapping MRI knee images were retrospectively collected and analyzed for 31 participants (9F/22M, 15.0 ± 3.8 years old) with JOCD lesions in the medial femoral condyle (MFC). In total, N  = 32 knees with JOCD lesions and N  = 14 control knees were assessed. Mean T2∗ values in four articular cartilage regions-of-interest (MFC, lateral femoral condyle (LFC), medial tibia (MT), and lateral tibia (LT)) and lesion volume were measured and analyzed using Wilcoxon-rank-sum tests and Spearman correlation coefficients ( R ). Results: Mean ± standard error T2∗ differences observed between the lesion-sided MFC and the LFC in JOCD-affected knees (28.5 ± 0.9 95% confidence interval [26.8, 30.3] vs 26.3 ± 0.7 [24.8, 27.7] ms, P  = 0.088) and between the affected- and control-knee MFC (28.5 ± 0.9 [26.8, 30.3] vs 28.5 ± 0.6 [27.1, 29.9] ms, P  = 0.719) were nonsignificant. T2∗ was significantly increased in the lesion-sided MT vs the LT for the JOCD-affected knees (21.5 ± 0.7 [20.1, 22.9] vs 18.0 ± 0.7 [16.5, 19.5] ms, P  = 0.002), but this same difference was also observed between the MT and LT in control knees (21.0 ± 0.6 [19.7, 22.3] vs 18.1 ± 1.1 [15.8, 20.4] ms, P  = 0.037). There was no significant T2∗ difference between the affected- and control-knee MT (21.5 ± 0.7 [20.1, 22.9] vs 21.0 ± 0.6 [19.7, 22.3] ms, P  = 0.905). T2∗ within the lesion-sided MFC was not correlated with patient age ( R  = 0.20, P  = 0.28) or lesion volume ( R  = 0.06, P  = 0.75). T2∗ values were slightly increased near lesions in later-stage JOCD subjects but without statistical significance. Conclusions: T2∗ relaxations times were not significantly different from control sites in the articular cartilage overlying JOCD lesions in the MFC or adjacent MT cartilage in early-stage JOCD.